ANALISIS LOGAM TIMBAL DAN TEMBAGA TERHADAP DAYA SERAP RUMPUT LAUT Gracilaria sp. SEBAGAI BIOSORBEN - Harahap, Muhammad Ridwan; Muammar Yulian; Akhi Nurul Agusti (AMINA, 2019)
Seaweed Gracilaria sp. is a water plant which is included into the red algae group (Rhodophyceae) which can potentially reduce the grade of metals Pb and Cu concentration. This research is aimed to know the heavy level of Pb and Cu metals which is adsorbed in seaweed Gracilaria sp. and the effect on the adsorption power of Pb and Cu metals based on variations in time of contamination. This research was done destructed by refluks destruction with resolvent HNO3: HClO4 (2:1) 15 mL. Thetime variations were 1, 2 and 3 weeks. The solvent of destruction obtained was measured by AAS (Atomic Absorption Spectrophotometer). The results are the grade of Pb metal on seaweed in the initial status concentration is obtained 1,2344 mg/L, 1,2820 mg/L in the first week, 1,2642 mg/L in the second week and 2,3149 mg/L in the third week. Based on the findings, it can be concluded that the grade levels of Pb Metal in seaweed Gracilaria sp. has already passed the BPOM No. 23 of 2017 standards setting is 0,20 mg/L. In the other hand, the grade levels of Cu metal on seaweed in the initial status concentration is obtained 0,0001 mg/L, 0,1579 mg/L in the first week, 0,5120 mg/L in the second week and 0.7946 mg/L in the third week. Based on the findings, it can be concluded that the grade level of Cu metal on seaweed Gracilaria sp. has already passed the limit which is conditioned by BPOM No. 03275/B/SK/VII/1989 is 0,1 mg/L.